Let the right one in? On European migration authorities' resistance to research. (30th July 2019) - Lindberg, Annika; Borrelli, Lisa Marie
Abstract : This article documents efforts to gain access to conduct ethnographic fieldwork in migration control agencies across eight European countries: Denmark, Finland, Germany, Italy, Latvia, Lithuania, Sweden and Switzerland. Building on repeated email exchanges, phone calls and fieldnotes from personal encounters between the researchers and state authorities, it traces and analyses state agencies' decisions on whether or not to let researchers in to study their practices. We found that our access negotiations, including failed ones, proved analytically useful, as they drew our attention to the fragmented nature of the state agencies we attempted to study, which contrasts with the order‐making functions they claim to perform within the field of border and migration control. From our observations emerges an image of 'the state' as made up by many hands and ridden by internal frictions, conflicting interests and values, which contributes to rendering state practices unpredictable and opaque, also to the street‐level officials enforcing them. This opacity of state bureaucracy has profoundly disempowering effects for those trying to access it, even if it is not necessarily consciously constructed. Instead, we show how our access negotiations drew attention to the ongoing struggles over power, knowledge and order within the contested field of migration control. Bien choisir qui laisser entrer? Sur la résistance des autorités migratoire européennes à la recherche: Cet article documente les efforts déployés pour obtenir l'autorisation d'effectuer des recherches ethnigraphiques au sein d'agences de contrôle migratoire de huit pays européens: le Danemark, la Finlande, l'Allemagne, l'Italie, la Lettonie, la Lituanie, la Suède et la Suisse. Fondé sur des échanges de courriels, des appels téléphoniques et des notes de terrain issues de rencontres personnelles entre les chercheurs et des autorités de l'État, l'article retrace et analyse les décisions des agences de l'État de laisser ou non des chercheuses étudier leurs pratiques. Nous avons constaté que nos négociations d'accès, y compris celles qui ont échoué, se sont révélées utiles sur le plan analytique, car elles ont attiré notre attention sur la nature fragmentée des agences d'État que nous tentions d'étudier, ce qui contraste avec les fonctions d'ordonnances qu'elles prétendent exercer dans le domaine des frontières et le contrôle de la migration. Nos observations dégagent une image de « l'État » composée de nombreuses mains et dominée par des frictions internes, des intérêts et des valeurs contradictoires, qui contribue à rendre les pratiques de l'État imprévisibles et opaques, également pour les agents d'interface qui l'incarnent. Cette opacité de la bureaucratie d'État a des effets profondément dissuasifs pour ceux qui tentent d'y accéder, même si elle n'est pas nécessairement construite consciemment. Nos négociations d'accès ont ainsi attiré notre attention sur les luttes autour du pouvoir, du savoir et de l'ordre dans le domaine contesté du contrôle migratoire.